RESEARCH OF UNMANNED DRIVING IN THE TRANSPORT INDUSTRY - Ворона, Даниил; Орел, Ольга (SWorldJournal, 2020)
Abstract. The article considers the history of autonomous vehicles development and features of their gradual improvement. The six levels of unmanned vehicle classification developed by the international organization SAE are listed. The specialized equipme